Gifted Education in the Australian Context. Issue 2 (April 2018) - Walsh, Rosalind L.; Jolly, Jennifer L.
The context in which gifted education operates in Australia provides for differing levels of identification and services. Lacking a federal mandate or funding, states and territories are responsible for addressing the needs of gifted students. Australia contributes to the gifted education research literature, focusing on acceleration, gifted girls, and teacher attitudes. The impacts of a relatively new national curriculum and assessment program have yet to be assessed in terms of their impact on gifted children. This article includes an overview of the policies, models, and barriers facing gifted education in Australia.